On the status of Umbilicaria aprina var. halei and U. canescens (Umbilicariaceae, lichenized Ascomycota) - Davydov, Evgeny A. (Phytotaxa, 2022)
To clarify the nomenclature of Umbilicaria aprina var. halei and U. canescens, type material from LE and MIN was investigated. Description, measurements and photos of the thalloconidia of the type specimens are provided. According to our investigation Umbilicaria aprina var. halei is a synonym of U. rhizinata, and U. canescens is a synonym of U. aprina. Both species belong to the U. aprina group and are distinguished by the septation of their thalloconidia. Additional specimens identified by previous authors as Umbilicaria aprina var. halei and U. canescens were re-identified. Umbilicaria rhizinata is reported as new to Xinjiang, China.